1996
DOI: 10.1183/09031936.96.09010054
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of fatal soybean dust-induced asthma

Abstract: A hypothesis was postulated that the characteristic clinical course of fatal soybean asthma may be reflected by specific immunopathological findings. Seven cases of fatal soybean dust-induced asthma from Barcelona, Spain were compared with 25 fatal asthma cases from New Zealand. Sections of lung tissue were stained by monoclonal antibodies using standard streptavidin-biotin peroxidase technique. The following cell types were identified: mast cells, "activated" eosinophils, neutrophils, monocytes/macrophages, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…These sudden fatal episodes may occur against a background of persistent airway inflammation and structural derangement; moreover, those with the most extreme structural changes, such as mucous gland hypetrophy, will have the most devastating response [50]. Patients with fatal soybean asthma have diminished numbers of CD3+ and CD8+ T-cells in the airway epithelium and submucosa compared with fatal asthma cases [51]. However, there were no differences in the numbers of mast cells, eosinophils and neutrophils in relation to basal asthma severity or to the pattern of fatal attack.…”
Section: Pathologymentioning
confidence: 99%
“…These sudden fatal episodes may occur against a background of persistent airway inflammation and structural derangement; moreover, those with the most extreme structural changes, such as mucous gland hypetrophy, will have the most devastating response [50]. Patients with fatal soybean asthma have diminished numbers of CD3+ and CD8+ T-cells in the airway epithelium and submucosa compared with fatal asthma cases [51]. However, there were no differences in the numbers of mast cells, eosinophils and neutrophils in relation to basal asthma severity or to the pattern of fatal attack.…”
Section: Pathologymentioning
confidence: 99%
“…Carroll et al [14] carefully examined the distribution of inflammatory cells throughout the bronchial tree of both fatal and nonfatal cases of asthma and showed increased numbers of lymphocytes and eosinophils uniformly distributed throughout the large and distal airways of mild and severe asthmatics when compared to control cases. Similar infiltration of T cells, macrophages, and eosinophils into the proximal and distal lung tissues has also been reported in rare cases of sudden asthma death (dying within 1 h after the onset of their symptoms) [15] and in soybean dust-induced asthma [20] .…”
Section: Inflammation In the Small Airwaysmentioning
confidence: 81%
“…Together with the recent applications of molecular pathological techniques, including immunocytochemistry and in situ hybridization to biopsies and bronchoalveolar lavage fluid, these technological advances have had a profound impact on our understanding of the pathogenesis of bronchial asthma [9,10] . Recent studies utilizing these approaches in surgically resected lung tissue [11][12][13] , postmortem lung specimens [14][15][16] , and transbronchial biopsies [17,18] have demonstrated that similar but more severe inflammatory and structural changes are also occurring in the distal lung [15,19,20] and extending into the lung parenchyma of asthmatic patients [17] .…”
mentioning
confidence: 99%
“…Some studies have indicated that the eosinophilic inflammatory response is worse in the proximal airways, with a redistribution of T-lymphocytes away from the airway epithelium, and others emphasize the even distribution of inflammation in both small and large airways [52,53]. Submucosal vascular congestion may also be an important feature.…”
Section: Pathologymentioning
confidence: 99%